Orbits of meaning construction in the Maghrebian film: A study in liberation concept - Elmahmoudi, Tarek Mohammed; Ghariani, Fethi (Journal of Humanities & Social Sciences, 2022)
The existence of the perception of liberation in cinema has a special character owing to the distinctiveness and privileges that the structure of this artistic expression has unlike other arts. The construction of the cinematic work hangs chiefly on the image, as it is the fundamental constituent of discourse and its language, the image unifies forms and meanings with content. As a result, it combines the narrative with the visual expressions in film depictions. So, the cinematic image is the artifact of interactions whose basis is predominantly intellectual. In other words, the making of sense and the refinement of meaning is essentially the base of image as well as its principle. In a word, meaning construction fixes the image level. Entwining the image leads to more research and penetration resulting in more indications and interpretations. The image can be an appearance of reality, but not always an imitator of that reality. Hence its structure ranges between reality and revelation. In order to develop the cinematic image and obtain its maximum potential, it was necessary for it to be liberated at all levels, reaching the deepest topics and the expectations of audience. This is merely made by heading in the direction of broad horizons of artistic and intellectual creativity, and inflowing worlds that were previously difficult to reach. Talking about the development of a cinema and its glow cannot be at hands without a free thought.